Adoption of faecal immunochemical testing for 2‐week‐wait colorectal patients during the COVID‐19 pandemic: an observational cohort study reporting a new service at a regional centre. (7th November 2020) - Maclean, William; Limb, Chris; Mackenzie, Paul; Whyte, Martin B.; Benton, Sally C.; Rockall, Timothy; Jourdan, Iain
Abstract: Aim: The COVID‐19 pandemic has resulted in the near‐complete loss of routine endoscopy services. We describe a major reorganization of service at a regional referral centre (Royal Surrey NHS Foundation Trust) to manage the crisis. Faecal immunochemical testing (FIT) was implemented for triage to make optimum use of limited diagnostic resources. Consultations were switched from face‐to‐face to telephone. Our aim was to evaluate the impact FIT had on resource allocation and patient diagnoses in the first 3 months of use. Method: All colorectal 2‐week‐wait patient referrals were posted a pack requesting FIT and notification of telephone consultation. A prepaid envelope was included for return of the samples. At consultation, FIT was incorporated with the presenting symptoms to guide the choice of investigation and triage urgency. FIT ≥10 μg/g was interpreted as positive. Outcome data were collected prospectively and compared with retrospective audit data from prepandemic levels across 3 months. Results: From 26 March 2020 to 2 July 381 patients were referred who were invited to provide FIT samples and underwent telephone consultations. Three hundred and fifty eight FIT samples were returned (94%). Onward referral for colonoscopy reduced from 62% to 34% ( P  < 0.001). There were 14 colorectal cancers (CRC) (3.7%) diagnosed, which was not statistically different from the prepandemic level of 3.9% ( P  = 0.995). Twelve of the 14 patients with a CRC diagnosis had provided samples; all 12 had FIT ≥10 μg/g and were offered fast‐track investigations. Conclusions: The incorporation of FIT optimized the allocation of limited resources to triage those who required urgent colonic investigation for detecting CRC.